Peningkatan keterampilan bertanya dan hasil belajar peserta didik melalui penerapan model problem based learning - Evi Susilowati; Suyatmi Suyatmi (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2019)
This study aims to improve questioning skill and Indonesian language learning outcomes through the application of Problem Based Learning models. The type of research used is classroom action research with two cycles through the planning, acting, observing and reflectioning stage. The results show that the application of Problem Based Learning can improve questioning skills and learning outcomes. This is shown in obtaining the results of asking skills by raising hands by 64%. Questioning skills with writing increased by 57%. Asking skills with friends increase by 47%. Similarly, inter-group questioning skills experienced an increase of 34%. The results of learning Indonesian in the first cycle of 57% increased to 90% in cycle 2.